Feed capable of preventing and treating gill rot disease of mandarin fish - WANG JUNFENG; GUO CHENGLI; TIAN SHOURONG (2017)
The invention discloses a feed capable of preventing and treating the gill rot disease of mandarin fish. The feed is prepared from the following components: parabramis pekinensis meal, corn meal, rape seed cakes, sesame seed meal, rice bran, tuchahoe powder, composite vitamin, amino acid, honeysuckles, monocalcium phosphate, starch, chlorite schist powder and a mulberry twig and trade route mixing extract. All the raw material components of the feed capable of preventing and treating the gill rot disease of the mandarin fish do not have any toxic and/or side effects; furthermore, by reasonable matching, the feed is rich in nutrition and high in palatability; the feeding quality of the mandarin fish is effectively improved, and the feed capable of preventing and treating the gill rot disease of the mandarin fish is extremely good. 本发明公开了种防治鳜鱼烂鳃病饲料，由以下成分制成：鳊鱼粉、玉米粉、菜籽饼、芝麻粕、米糠、茯苓粉、复合维生素、氨基酸、金银花、磷酸二氢钙、淀粉、礞石粉、桑树嫩枝与商路混合提取物。本发明种防治鳜鱼烂鳃病饲料各原料组分均无任何毒副作用，且通过合理搭配使其营养丰富且适口性好，有效的提高了鳜鱼的喂食质量，对鳜鱼烂鳃病防治效果极佳。